Children with Chronic Hepatitis B in the US and Canada - Schwarz, Kathleen B (J Pediatr, 2015)
OBJECTIVES: To test the hypothesis that children with chronic hepatitis B (CHB) living in the US and Canada would also have international origins and characteristic hepatitis B virus (HBV) genotypes and laboratory profiles. STUDY DESIGN: Clinical characteristics of children enrolled in the HBRN were collected from 7 US and Canadian centers. RESULTS: Children (n=343) with an age range of 1.0 – 17.8 years were enrolled; 78% of the children were Asian, 55% were adopted and 97% had international origins with either the child or a parent born in one of 31 countries. The majority had hepatitis B virus (HBV) genotype B (43%) or C (32%), and the remainder had genotype A (5%), D (16%), E (4%), or multiple (<1%). Children with genotype B or C were Asian (98% and 96%), more consistently hepatitis B e antigen (HBeAg) positive (95% and 82%), had higher median HBV DNA levels (8.2 and 8.3 log(10) IU/mL), and less frequently had elevated alanine aminotransferase values (43% and 57%) compared with children with other genotypes. The percentage of HBeAg positivity and of those with HBV DNA ≥6 log(10) IU/mL declined with age. CONCLUSIONS: The majority of children in the HBRN have HBV genotypes which reflect their international origins. Clinical and laboratory data differ substantially by patient age and HBV genotype. Use of these data can help drive the development of optimal strategies to manage and treat children with CHB.